Contrasting effects of agriculture and urban land use on macroinvertebrate secondary production in Neotropical streams - Björn Gücker; Mario Brauns; Alexandre T.B. Santos; Ana P.C. de Carvalho; Iola G. Boëchat (Ecological Indicators, 2024)
We compared the structural and functional attributes of Neotropical macroinvertebrate communities between two natural, two agricultural, and two urban streams. We quantified food resource availability, community structure, secondary production, and consumer–resource interaction strength, attributing them to environmental characteristics. In agricultural streams, secondary production was significantly reduced compared to natural streams, reaching the lowest reported estimates for tropical streams (0.08–0.69 g DW·m−2·year−1 in agricultural streams vs. 1.1–15.8 g DW·m−2·year−1 in natural streams). This decline was primarily attributed to habitat degradation caused by siltation and channelization, alongside stronger top-down pressure in agricultural streams. Conversely, urban streams exhibited a substantial increase in secondary production, ranking among the highest estimates for tropical streams (25.6–191.2 g DW·m−2·year−1). The high secondary production in urban streams was primarily due to substantial increases in fine benthic organic matter, likely originating from poorly treated wastewater. Along with higher resource availability, we also observed a lack of, or insufficient, top-down control by macroinvertebrate predators or fish, which may have promoted higher secondary production in urban streams. This study is the first to quantify land use impacts on energy flows in stream communities in a region particularly threatened by land use change. Future studies should address multifunctional responses to land use changes in both the tropical and temperate realms to shed new light on how stream ecosystem functions in different biomes respond to human impacts. Our findings highlight the urgent need for effective management strategies tailored to address the environmental characteristics of tropical stream ecosystems.